Ayat-Ayat Terkait Akad Transaksi: Kajian Tematik Dalam Perspektif Ekonomi Islam - Sufiani Zahra; Muh Affandi; Rahman Ambo Masse; Nasrullah Sapa (Jurnal Ekonomi dan Bisnis Digital, 2025)
Contracts are the main foundation in all forms of muamalah transactions in Islam. The Qur'an as the main source of Islamic teachings has provided clear guidance regarding the principles and rules governing various types of contracts. This study aims to examine the verses of the Qur'an that are directly related to transaction contracts, both general and specific to certain types of transactions such as buying and selling, debts, and cooperation. The method used in this study is a qualitative study with a thematic interpretation approach (maudhu'i). The results of the study show that the Qur'an not only regulates the validity of contracts, but also guarantees justice, transparency, and willingness in transactions. This study is expected to be a conceptual reference in building a fair and sustainable Islamic economic system.